High-resolution total inorganic carbon data from IODP Site 342-U1403, Newfoundland Margin - Alexa Fischer; Sietske J Batenburg; André Bahr; Silke Voigt; Anne Rheinberger; Sarah Schmickal; Silvia Rheinberger; Markus Greule; Stefan Rheinberger; Oliver Friedrich (PANGAEA, 2025)
This dataset lists the results of TIC measurements from International Ocean Discovery Program (IODP) Site U1403 off Newfoundland (~40°N, 51°W; 4944 m water depth, Expedition 342, NW Atlantic Ocean). The TIC content was analyzed on bulk sediment using a Shimadzu Total Organic Carbon Analyzer.